دور الرقابة الإدارية في تطوير الأداء التنظيمي للمنظمات - ذيب,حمه; جاهمي,عبدالعزيز (University of Eloued جامعة الوادي, 2024)
Abstract: Administrative control is one of the most important processes through which organizations seek to achieve their continuity, success and development of their organizational performance within organizations, and presenting a theoretical framework that identifies and defines the various concepts related to them, and it has been concluded that administrative control has an effective role in improving performance within the organization, as its existence is associated with the accuracy of business completion, and raising the level of performance and discipline, through defining performance standards, measuring performance The actual comparison and evaluation of the deviation and taking corrective action, in addition to the contribution of technology in strengthening administrative control. تعد الرقابة الإدارية من أهم العمليات التي تسعى المنظمات من خلالها إلى تحقيق إستمرارها ونجاحها وتطوير أدائها التنظيمي، ويعتبر المورد البشري محل إهتمام خاصة وأنه العنصر الأساسي في تحقيق الأهداف المنشودة بدرجة عالية من الكفاءة والفعالية، وتهدف هذه الدراسة إلى تحديد دور الرقابة الإدارية في تطوير الأداء التنظيمي داخل المنظمات، وتقديم إطار نظري يحدد ويعرف مختلف المفاهيم المتعلقة بهما، وقد تم التوصل إلى أن الرقابة الإدارية لها دور فعال في تحسين الأداء داخل التنظيم، حيث يتلازم وجودها مع دقة إنجاز الأعمال، ورفع مستوى الأداء والإنضباط، من خلال تحديد معايير الأداء، قياس الأداء الفعلي و مقارنة وتقييم الإنحراف و إتخاذ الإجراءات التصحيحة،إضافة إلى مساهمة التكنولوجيا في تعزيز الرقابة الإدارية.
Keywords: أداء تنظيمي; رقابة إدارية; قياس الأداء الفعلي; تقييم الإنحراف; organizational performance; Administrative control; Actual performance measurement; Deviation assessment; administration